Fetch the Bolt Cutters, We’ve Been in Here for Too Long: An Analytical History of Women’s Resistance to Patriarchal Systems in Nigeria 1912-1976 - Angelica Smith, Angelica (The Toro Historical Review, 2021)
Abstract: The paper reviews the history of Nigerian Women's suppression. From an earlier focus on women's suppression in the histories of religion, marriage, and education, this work takes on more recent studies by analyzing spheres of political participation to reveal the historical imbalance of women in political positions. This historiography counters previous work by the scholar, acknowledging women's advocacy for participation in domains traditionally dominated by men. The work will consider how historians have studied women's participation with focuses on female political events like Igbo Women's Riots, female participation in the independence of Nigeria, and finally, women's suffrage. By analyzing women's participation in the Northern and Southern provinces of Nigeria side by side rather than together, we can see how women from each protectorate existed differently under patriarchal systems until their subsequent suffrage in 1976. This work aims to improve our knowledge of Nigerian women existing within the binds of male domination and the attempted acts of dismantling it.